Family Functioning and Resilient Coping in Peruvian Parents : a Study Conducted during the COVID-19 Pandemic - Callupe Laura, Elizabeth (2022)
In order to determine whether family functioning predicts the level of resilience in parents facing the impact of the COVID-19 pandemic, a predictive and cross-sectional study was conducted on a sample of 183 parents from the department of La Libertad, who were selected under a non-probabilistic purposive sampling. Two instruments were used to collect data: Cohesion and Family Adaptability Evaluation Scale (CESF) and the Brief Resilient Coping Scale (BRC). Based on a linear regression analysis, an adequate model fit is observed (F-test = 35.924, p < .001), where, family functioning (β = .407, p < .05) is a variable that significantly predicts resilience (adjusted R2 = .161). Also, the t-values of the beta regression coefficients of the predictor variable are highly significant (p < .01). In conclusion, the level of family functioning predicts the degree of resilient coping in parents in the department of La Libertad during the COVID-19 pandemic.